Controlled One‐pot Synthesis of Nickel Single Atoms Embedded in Carbon Nanotube and Graphene Supports with High Loading. Issue 7 (29th April 2020) - Zhao, Shiyong; Wang, Tianshuai; Zhou, Guangmin; Zhang, Liji; Lin, Chao; Veder, Jean‐Pierre; Johannessen, Bernt; Saunders, Martin; Yin, Lichang; Liu, Chang; De Marco, Roland; Yang, Shi‐Ze; et al.
Abstract: Single‐atom catalysts (SACs) have attracted much attentions due to the advantages of high catalysis efficiency and selectivity. However, the controllable and efficient synthesis of SACs remains a significant challenge. Herein, we report a controlled one‐pot synthesis of nickel single atoms embedded on nitrogen‐doped carbon nanotubes (NiSA−N−CNT) and nitrogen‐doped graphene (NiSA−N−G). The formation of NiSA−N−CNT is due to the solid‐to‐solid rolling up mechanism during the high temperature pyrolysis at 800 °C from the stacked and layered Ni‐doped g‐C3 N4, g‐C3 N4 −Ni structure to a tubular CNT structure. Addition of citric acid introduces an amorphous carbon source on the layered g‐C3 N4 −Ni and after annealing at the same temperature of 800 °C, instead of formation of NiSA−N−CNT, Ni single atoms embedded in planar graphene type supports, NiSA−N−G were obtained. The density functional theory (DFT) calculation indicates the introduction of amorphous carbon source substantially reduces the structure fluctuation or curvature of layered g‐C3 N4 ‐Ni intermediate products, thus interrupting the solid‐to‐solid rolling process and leading to the formation of planar graphene type supports for Ni single atoms. The as‐synthesized NiSA−N−G with Ni atomic loading of ∼6 wt% catalysts shows a better activity and stability for the CO2 reduction reaction (CO2 RR) than NiSA−N−CNT with Ni atomic loading of ∼15 wt% due to the open and exposed Ni single atom active sites in NiSA−N−G. This study demonstrates for the first time the feasibility in the control of the microstructure of carbon supports in the synthesis of SACs. Abstract : Singled out : We have demonstrated the feasibility of the controlled one‐pot synthesis of Ni single‐atom catalysts through introducing an amorphous carbon source to stabilize and control the transformation of layered g‐C3N4‐Ni to Ni single atoms embedded in tubular CNTs or planar graphene, NiSA−N−CNT and NiSA−N−G. NiSA−N−G shows a high activity for carbon dioxide reduction.